Persistent Salmonella enterica Serovar Typhimurium Infection Induces Protease Expression During Intestinal Fibrosis. Issue 10 (9th May 2019) - Ehrhardt, Katrin; Steck, Natalie; Kappelhoff, Reinhild; Stein, Stephanie; Rieder, Florian; Gordon, Ilyssa O; Boyle, Erin C; Braubach, Peter; Overall, Christopher M; Finlay, B Brett; Grassl, Guntram A
Abstract: Background: Intestinal fibrosis is a common and serious complication of Crohn's disease characterized by the accumulation of fibroblasts, deposition of extracellular matrix, and formation of scar tissue. Although many factors including cytokines and proteases contribute to the development of intestinal fibrosis, the initiating mechanisms and the complex interplay between these factors remain unclear. Methods: Chronic infection of mice with Salmonella enterica serovar Typhimurium was used to induce intestinal fibrosis. A murine protease-specific CLIP-CHIP microarray analysis was employed to assess regulation of proteases and protease inhibitors. To confirm up- or downregulation during fibrosis, we performed quantitative real-time polymerase chain reaction (PCR) and immunohistochemical stainings in mouse tissue and tissue from patients with inflammatory bowel disease. In vitro infections were used to demonstrate a direct effect of bacterial infection in the regulation of proteases. Results: Mice develop severe and persistent intestinal fibrosis upon chronic infection with Salmonella enterica serovar Typhimurium, mimicking the pathology of human disease. Microarray analyses revealed 56 up- and 40 downregulated proteases and protease inhibitors in fibrotic cecal tissue. Various matrix metalloproteases, serine proteases, cysteine proteases, and protease inhibitors were regulated in the fibrotic tissue, 22 of which were confirmed by quantitative real-time PCR. Proteases demonstrated site-specific staining patterns in intestinal fibrotic tissue from mice and in tissue from human inflammatory bowel disease patients. Finally, we show in vitro that Salmonella infection directly induces protease expression in macrophages and epithelial cells but not in fibroblasts. Conclusions: In summary, we show that chronic Salmonella infection regulates proteases and protease inhibitors during tissue fibrosis in vivo and in vitro, and therefore this model is well suited to investigating the role of proteases in intestinal fibrosis. Abstract : We demonstrate that chronic Salmonella infection induces intestinal tissue inflammation and fibrosis and regulates a large number of proteases and protease inhibitors. The pattern of protease expression resembles the pattern seen in the fibrotic intestine of IBD patients.